Evaluation of the NLRP3 Inflammasome Activating Effects of a Large Panel of TiO2 Nanomaterials in Macrophages - Julia Kolling (Nanomaterials, 2020)
TiO2 nanomaterials are among the most commonly produced and used engineered nanomaterials (NMs) in the world. There is controversy regarding their ability to induce inflammation-mediated lung injuries following inhalation exposure. Activation of the NACHT, LRR and PYD domains-containing protein 3 (NALP3) inflammasome and subsequent release of the cytokine interleukin (IL)-1β in pulmonary macrophages has been postulated as an essential pathway for the inflammatory and associated tissue-remodeling effects of toxic particles. Our study aim was to determine and rank the IL-1β activating properties of TiO2 NMs by comparing a large panel of different samples against each other as well as against fine TiO2, synthetic amorphous silica and crystalline silica (DQ12 quartz). Effects were evaluated in primary bone marrow derived macrophages (BMDMs) from NALP3-deficient and proficient mice as well as in the rat alveolar macrophage cell line NR8383. Our results show that specific TiO2 NMs can activate the inflammasome in macrophages albeit with a markedly lower potency than amorphous SiO2 and quartz. The heterogeneity in IL-1β release observed in our study among 19 different TiO2 NMs underscores the relevance of case-by-case evaluation of nanomaterials of similar chemical composition. Our findings also further promote the NR8383 cell line as a promising in vitro tool for the assessment of the inflammatory and inflammasome activating properties of NMs.